Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(3x^2-5x-8\)
\(=3x^2+3x-8x-8\)
\(=3x\left(x+1\right)-8\left(x+1\right)\)
\(=\left(x+1\right)\left(3x-8\right)\)
b) \(x^4+6x^3+9x^2-16\)
\(=\left(x^2+3x\right)^2-16\)
\(=\left(x^2+3x-4\right)\left(x^2+3x+4\right)\)
\(=\left(x^2-x+4x-4\right)\left(x^2+3x+4\right)\)
\(=\left[x\left(x-1\right)+4\left(x-1\right)\right]\left(x^2+3x+4\right)\)
\(=\left(x-1\right)\left(x+4\right)\left(x^2+3x+4\right)\)
a) 4x2 - 20x + 25 - 36y2
= (2x - 5)2 - 36y2
= (2x - 5 - 6y)(2x - 5 + 6y)
b) x3 + x2 - 2x - 8
= (x3 - 8) + (x2 - 2x)
= (x - 2)(x2 + 2x + 4) + x(x - 2)
= (x - 2)(x2 + 2x + 4 + x)
= (x - 2)(x2 + 3x + 4)
d) x4 + 6x3 + 9x2 - 16
= x2(x2 + 6x + 9) - 16
= x2(x + 3)2 - 16
= (x2 + 3x)2 - 16
= (x2 + 3x - 4)(x2 + 3x + 4)
= (x2 + 4x - x - 4)(x2 + 3x + 4)
= [x(x + 4) - (x + 4)](x2 + 3x + 4)
= (x - 1)(x + 4)(x2 + 3x + 4)
a) \(2x\left(x-3\right)^2+5x\left(3-x\right)\)
\(=2x\left(x-3\right)^2-5x\left(x-3\right)\)
\(=\left(x-3\right)\left[2x\left(x-3\right)-5x\right]\)
\(=\left(x-3\right)\left(2x^2-6x-5x\right)\)
\(=\left(x-3\right)\left(2x^2-11x\right)\)
\(=x\left(x-3\right)\left(2x-11\right)\)
b) \(\left(x+3\right)^2-4\left(y^2-2y+1\right)\)
\(=\left(x+3\right)^2-2^2\left(y-1\right)^2\)
\(=\left(x+3\right)^2-\left[2\left(y-1\right)\right]^2\)
\(=\left[\left(x+3\right)-2\left(y-1\right)\right]\left[\left(x+3\right)+2\left(y-1\right)\right]\)
\(=\left(x+3-2y+2\right)\left(x+3+2y-2\right)\)
\(=\left(x-2y+5\right)\left(x+2y+1\right)\)
a) \(2x.\left(x-3\right)^2+5x.\left(-x+3\right)=2x.\left(x-3\right)^2-5x.\left(x-3\right)\)
\(=\left(x-3\right).\left(2x^2-11x\right)=\left(x-3\right).x.\left(2x-11\right)\)
b) \(\left(x+3\right)^2-4.\left(y^2-2y+1\right)=\left(x+3\right)^2-2^2.\left(y-1\right)^2\)
\(=\left(x+3\right)^2-\left[2.\left(y-1\right)\right]^2=\left(x-2y+1\right).\left(x+2y+5\right)\)
\(\left(x^2-5x+8\right)^2-6x+8\)
\(=x^4+25x^2+64-10x^3-80x+16x^2-6x+8\)
\(=x^4-10x^3+41x^2-86x+72\)
\(=x^3\left(x-2\right)-8x^2\left(x-2\right)+25x\left(x-2\right)-36\left(x-2\right)\)
\(=\left(x-2\right)\left(x^3-8x^2+25x-36\right)\)
\(=\left(x-2\right)\left[x^2\left(x-4\right)-4x\left(x-4\right)+9\left(x-4\right)\right]\)
\(=\left(x-2\right)\left(x-4\right)\left(x^2-4x+9\right)\)